Development Of Palm Kernel Oil Polyol - Based Shape Memory Polyurethane With Polyethylene Glycol (Peg) And Poly Caprolactone (Pcl) As Soft Segment - Nguyen, Hoang Trinh (2019)
Shape memory polyurethanes (SMPU) is one of the most notable and common shape memory polymer (SMP), and its composites has gained attention due to the enhancement in both shape memory and mechanical properties. In addition, as the awareness of sustainable development, environmental issues, and fossil fuel depletion, palm kernel oil polyol (PKO-p) - based SMPU and its relative composite reinforced with graphene nanoplatelets (GNPs) were synthesized and characterized in this study. Both SMPU and its composite samples were fabricated using two-step pre-polymerization method. A series of SMPU with different type, molecular weight (MW), and molar ratio of long chains polyol (polycaprolactone diol (PCL) and polyethylene glycol (PEG)) was synthesized and analyzed. The results pointed out that PU-PEG samples (PKO-p - based SMPU with PEG as the long chain polyol) exhibited better shape fixity but low tensile strength which is due to the high crystallinity of PEG and extremely high degree of phase separation (DPS) whereas PU-PCL samples (PKO-p - based SMPU with PCL as the long chain polyol) were not able to show shape fixability but exhibited better tensile strength and flexibility due to the effect of phase mixing. The type of polyols attributed significantly to the shape memory properties while the MW had a slight effect on its properties. PU-PCLPEG samples with the combination of PCL and PEG as soft segments overcame the drawbacks of PU-PCL and PU-PEG samples. For the fabrication of SMPU composites, GNPs was functionalized by acid treatment and evaluated using several analyses (Fourier transform infra-red, Zeta potential, Filed-emission scanning electron microscope, Raman spectroscopy) before incorporating with pre-polymer to produce the composites (varies at 0.25, 0.5, 1.0, 1.5wt% of GNP). With the presence of oxygen-containing functional groups introduced during acid treatment process, treated GNPs dispersed and distributed in polyurethane (PU) matrix was better than the composite with un-treated GNPs, hence results in a remarkable enhancement in mechanical properties, especially the tensile strain at break. Functionalized GNP - based SMPU composite (PU-F) reached maximum tensile strength at 1wt% of functionalized GNP, which is 150% higher compared to that of neat SMPU while tensile strain at break increased 1590% than that of neat SMPU at 0.25wt% functionalized GNP. In contrary, there was a reduction on the modulus of PU-F samples compared with the pristine SMPU, and the modulus was improved significantly when the amount of functionalized GNP reached 1wt%. With regards to the shape properties of all composites, shape fixity was almost similar to that of neat SMPU and all the composite samples recovered completely to their original shape with 100% shape recovery.